An Evaluation of the Correlation between Criminal Intelligence Management and Security Operations in Benue State, Nigeria. - Featherstone, Clairmont (Indonesian Journal of Counter Terrorism and National Security, 2023)
This study examined the correlation between criminal intelligence management and security operations in Benue State, North Central Nigeria. The study adopted the qualitative method, semi-structured Key Information Interview (KII) technique and review of relevant literature in its investigations. Based on its earlier findings, the following conclusions were reached by the study. A sample size of 21 (n-21) was determined for the study. Findings of the study showed that the way the key tools/agents used for collection of intelligence information for production of criminal intelligence, including informants, surveillance, technologies (ICTs), and community policing, has significant correlation with the outcome of security operations by the Joint Task Force and other outfits involved in the fight against crime in Benue State. Secondly, this study also found that how criminal intelligence analysis phase of the intelligence cycle (process) is managed has significant relationship with the outcome of security operations by the Joint Task Force and other outfits involved in the fight against the rising wave of crime in Benue State. Furthermore, it was also the finding of this study that the way dissemination/sharing of criminal intelligence products among sister anti-crime outfits is managed has significant correlation with the outcome of security operations involved in the fight against crime in Benue State. Another recommendation of the study was adequate provision of operational logistics to the Intelligence Units of various law enforcement agencies, including patrol vehicles, telephones, and other communication equipment, arms and ammunition, and cameras, among others. The study also recommended great efforts at enhancing the capacities of the community policing approach to fighting crime by way of adequate provision of operational logistics, enhanced remuneration, and regular training of volunteers in the various vigilante groups operating across various local and urban neighbourhoods in Nigeria, including the Livestock Guards in Benue State.